PENGARUH PENGETAHUAN PERPAJAKAN, SANKSI PAJAK, DAN SOSIALISASI TERHADAP KEPATUHAN WAJIB PAJAK UMKM DI KOTA BATAM - Sela; Haposan Banjarnahor (LPPM Universitas Putera Batam, 2026)
Registered MSME units in Batam City, Indonesia increased rapidly from 27,625 (2022), 31,720 (2023), to 35,256 (2024) according to Batam Cooperative Office data, yet SPT reporting rates remained suboptimal at 10.1%, 11.84%, and 15.27%. Nationally, 65 million MSMEs absorb 97% workforce and contribute 61% GDP, but tax contributions lag due to limited tax knowledge, weak sanction enforcement, and inadequate socialization. This study examines the influence of tax knowledge, tax sanctions, and tax socialization on MSME taxpayer compliance using quantitative approach with population of 35,256 MSMEs, 100 respondents sampled via Slovin's formula (10% margin error) through purposive sampling, validated Likert-scale questionnaires analyzed by multiple linear regression in SPSS following validity, reliability, and classical assumption tests.T-test results show tax knowledge (β=0.199, p=0.004), tax sanctions (β=0.197, p=0.018), and socialization (β=0.488, p<0.001) significantly influence taxpayer compliance individually. F-test confirms simultaneous influence (F=113.286, p<0.001, R²=0.784)